2022
DOI: 10.1001/jamainternmed.2021.6745
|View full text |Cite
|
Sign up to set email alerts
|

Time to Benefit of Bisphosphonate Therapy for the Prevention of Fractures Among Postmenopausal Women With Osteoporosis

Abstract: IMPORTANCEThe clinical decision to initiate bisphosphonate therapy for the treatment of osteoporosis requires balancing shorter-term harms and burdens (eg, gastroesophageal irritation or severe musculoskeletal pain) with longer-term benefits in reducing potential fractures.OBJECTIVE To assess the time to benefit (TTB) of bisphosphonate therapy for the prevention of nonvertebral and other fractures among postmenopausal women with osteoporosis.DATA SOURCES Randomized clinical trials (RCTs) were identified from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 70 publications
0
42
0
1
Order By: Relevance
“…Pharmacological aspects of the AOM include time to treatment onset and size of treatment fracture risk reduction. Bisphosphonates vary in their time to maximal fracture reduction with a weak effect from 4 months and a maximal effect requiring at least 12 months in general [39] with differences by fracture type and type of bisphosphonate [40]. A head-to-head trial with fracture end points has demonstrated the superiority of anabolic to anti-resorptive AOMs [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological aspects of the AOM include time to treatment onset and size of treatment fracture risk reduction. Bisphosphonates vary in their time to maximal fracture reduction with a weak effect from 4 months and a maximal effect requiring at least 12 months in general [39] with differences by fracture type and type of bisphosphonate [40]. A head-to-head trial with fracture end points has demonstrated the superiority of anabolic to anti-resorptive AOMs [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported high-certainty evidence that bisphosphonates are beneficial for reducing the risk of VFs with data extending to 2 years, in particular with moderate-certainty evidence that these medications are beneficial for preventing and treating corticosteroid-induced bone loss at the lumbar spine and femoral neck, with little to no harm [ 22 ]. Similarly, a more recent meta-analysis revealed that bisphosphonate therapy is most likely to benefit postmenopausal women with osteoporosis who have a life expectancy greater than 12.4 months, but this may be a limiting factor in this population [ 23 ]. All patients with a high risk of corticosteroid induced bone loss should be counseled on lifestyle measures to maintain bone strength including nutrition and weight-bearing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the optimal maximum time to stay on bisphosphonates is 3-5 years, but how long does it take for the benefits to kick in? The answer is just over a year, according to this meta-analysis involving over 23 000 postmenopausal women with osteoporosis, which found that it took 12.4 months to avoid one non-vertebral fracture per 100 women who took bisphosphonates 1. To prevent one hip fracture, 200 women would need to be taking bisphosphonates for 20.3 months, and 200 women would need to be on them for one year to avoid one clinical vertebral fracture.…”
Section: Living Long Enough To Benefit From Treatmentmentioning
confidence: 99%